The original source, structure and content of al-Farabi’s treatise “Al-Wahid wa-l-Wahda” (On One and Unity) (Journal of Oriental Studies, 2020)
To date, the treatises of Abu Nasr al-Farabi inherited by us, have not yet fully introduced into scientific use. Even scholars disagree about the number of his treatises (We will discuss more this issue in a separate article). Al-Farabi’s treatise, Al-Wahid wa-l-Wahda (On One and Unity), was first published in 1989 in Casablanca along with its scholarly analysis in Arabic. One of the scholars who compared the manuscripts and wrote the foreword and worked diligently to introduce this work for scientific use is the Iraqi scholar Muhsin Mahdi. Al-Farabi’s treatise “Al-Wahid wa-l-Wahda” was translated into Turkish in 2008 by Dr. Zhevdet Kylysh, the member of the faculty of Frat University. In addition, it is known that among the available sources, there is a voluminous analytical article by Damien Janos in English entitled “Al-Fārābī’s (d. 950) On the One and Unity Some Preliminary Remarks on Its Structure, Contents, and Theological Implications”. According to our research, this treatise has not yet been translated into Kazakh and Russian. Therefore, this article for the first time presents al-Farabi’s treatise “Al-Wahid wa-l-Wahdah” in the Kazakh language and for the first time its structure and content were analyzed. Key words: Al-Farabi, source, al-Wahid wal-wahda, original text, translation.